The experiences of 585 people when they tried to withdraw from antipsychotic drugs - John Read (Addictive Behaviors Reports, 2022)
Introduction: Many recipients of antipsychotic drugs try to stop taking them, primarily because of distressing adverse effects. Little research has been undertaken into the withdrawal symptoms that ensue. Methods: In an online survey 585 antipsychotic users, from 29 countries, who had tried to stop taking the drugs, were asked specific questions about the process and the open question: ‘What were the effects of withdrawing from the medication?’ 44% had a diagnosis in the ‘schizophrenia’ spectrum. Results: Responding to specific questions, 72% reported classical withdrawal effects of the kind associated with other central nervous system medications, including nausea, tremors, anxiety, agitation and headaches. 52% of these categorized those effects as ‘severe’. 26% had tried four or more times to discontinue, and 23% took at least one year to successfully withdraw completely. In response to the open question, 73% reported one or more withdrawal effects, most frequently, insomnia, nervousness and extreme feelings; 26% reported one or more positive outcomes, most frequently more energy/alive and clearer thinking; and 18% reported psychosis. Conclusion: These findings are consistent with a small but growing body of literature on this topic. Prescribers need to inform themselves about the nature, frequency and intensity of withdrawal effects from APs, and about withdrawal psychosis. National guidelines, professional bodies’ statements, and drug company information urgently need to be updated to prevent the suffering that can occur when withdrawal is minimised, misunderstood or unsupported.